“It's something you can't wash off; you carry it with you”: a qualitative study into teachers' experiences of vicarious trauma symptoms during the COVID-19 pandemic in Victoria, Australia - Crivari, Olivia; Oxford, Sarah; Schroder, Carmen; Anderson, Sarah; McMillan, Janine (Frontiers in Education, 2025)
BackgroundThe COVID-19 pandemic caused unprecedented disruption to education systems worldwide, and exacerbated existing challenges in the teaching profession. The dual demands of academic instruction and pastoral care placed a considerable amount of emotional burden on teachers, compounded by increased exposure to the traumatic experiences of students. This heightened risk of vicarious trauma among teachers has been underexplored, particularly in the context of Victoria, Australia, where one of the world's longest government-mandated lockdowns was implemented.MethodsThis study builds on previous research by examining how teachers' roles and responsibilities informally evolved in response to external pressures during the pandemic. Drawing on interview and focus group data from 25 educators in public and private schools across Victoria in 2022, the findings were coded via NVIVO software version 12 and thematically analyzed.ResultsFindings suggest that roles of educators evolved during the pandemic as their responsibilities expanded beyond academic instruction to include more pastoral care for students. This, in turn, disclosed different pathways through which educators were exposed to traumatic content from their students, families and other educators. As a result, many participants felt vicarious trauma symptoms, which is explored as various negative emotions.ConclusionThis study highlights the risk of vicarious trauma becoming an issue within the teaching profession. It underscores the need for further research to understand how vicarious trauma is affecting the teaching profession.